2022
DOI: 10.1038/s41598-022-26954-w
|View full text |Cite
|
Sign up to set email alerts
|

Expression profiles of small non-coding RNAs in breast cancer tumors characterize clinicopathological features and show prognostic and predictive potential

Abstract: Precision medicine approaches are required for more effective therapies for cancer. As small non-coding RNAs (sncRNAs) have recently been suggested as intriguing candidates for cancer biomarkers and have shown potential also as novel therapeutic targets, we aimed at profiling the non-miRNA sncRNAs in a large sample set to evaluate their role in invasive breast cancer (BC). We used small RNA sequencing and 195 fresh-frozen invasive BC and 22 benign breast tissue samples to identify significant associations of s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 66 publications
3
4
0
Order By: Relevance
“…In addition to finding a correlation of the DE of sncRNAs with patient metastasis status, we found that a large number of sncRNAs correlated with various clinicopathological features, especially tumor grade, lymphovascular invasion, tumor focality and breast cancer molecular subtypes, in agreement with a recent study [29]. Interestingly, we have also described SNORD124 up-regulation in tumors expressing HER2, suggesting that SNORD124 could serve as a diagnostic biomarker for HER2-positive tumors.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…In addition to finding a correlation of the DE of sncRNAs with patient metastasis status, we found that a large number of sncRNAs correlated with various clinicopathological features, especially tumor grade, lymphovascular invasion, tumor focality and breast cancer molecular subtypes, in agreement with a recent study [29]. Interestingly, we have also described SNORD124 up-regulation in tumors expressing HER2, suggesting that SNORD124 could serve as a diagnostic biomarker for HER2-positive tumors.…”
Section: Discussionsupporting
confidence: 91%
“…We therefore could not address the relative expression of the DE sncRNAs found in our study compared to normal breast tissue, which would have help to elucidate whether the studied sncRNAs act as oncogenes or TSG. However, three DE sncRNAs associated with locoregional metastases SNORA80E, SNOR15B and SNORD114-20 have been previously reported to be deregulated in invasive local BC compared to benign breast tissue [29]. Second, our biological significance and enrichment analyses-based on various databases that included host genes, target genes and interactions between genes and sncRNAs from the TCGA-BRCA atlas-showed similar signaling pathways as those described in the literature [20,30].…”
Section: Discussionsupporting
confidence: 73%
“…Supporting a role for Nm in cancer, FBL and snoRNAs are overexpressed across multiple tumor types ( Su et al 2014 ; Gong et al 2017 ; Barros-Silva et al 2021 ; Kärkkäinen et al 2022 ). Moreover, knockdown of box C/D snoRNP components including FBL, NOP56, and NOP58 decreases the tumorigenicity of breast cancer cell lines ( Su et al 2014 ).…”
Section: Disease Relevance Of Nmmentioning
confidence: 99%
“…MiRNA are short 20-22 nucleotide RNA sequences that upon binding to complementary regions (seeds) on target mRNA molecules affect their transcription leading in the majority of cases to its inhibition by inducing RNA degradation or inhibiting its translation. Sequencing of patients derived material highlighted multiple miRNA, which could serve as prognostic markers and/or predict treatment response, for example to radiotherapy (RT) and/or tamoxifen in BC patients ( 37 ), to RT in prostate cancer ( 38 ) and to cisplatin in lung cancer ( 39 ).…”
Section: Search For Biomarkers For Patient Stratificationmentioning
confidence: 99%